2021
DOI: 10.1037/sah0000334
|View full text |Cite
|
Sign up to set email alerts
|

Factors linking perceived discrimination and weight bias internalization to body appreciation and eating pathology: A moderated mediation analysis of self-compassion and psychological distress.

Abstract: Stigma and recurrent discriminatory experiences can lead to distress and internalization of biases. Self-compassion is a widely recognized resilience factor that may decrease the impact of discrimination on psychological well-being. Research highlights the potential utility of self-compassion in counteracting the harmful effects of discrimination, reducing psychological distress, and preventing the development of eating disorders. The present study examined the roles of self-compassion and psychological distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Both groups showed and implicit and explicit preference towards persons with normal weight relative to persons with overweight. Thus, our results confirm that persons with overweight and obesity indeed internalize the disadvantaged societal attitudes towards their own ingroup as shown in previous research using explicit selfreport measures (Macho et al, 2021;Pullmer et al, 2021). Interestingly, there was an inverse correlation between BMI and implicit weight bias score, which means that persons with higher BMI showed this preference to a lesser extent.…”
Section: Discussionsupporting
confidence: 90%
“…Both groups showed and implicit and explicit preference towards persons with normal weight relative to persons with overweight. Thus, our results confirm that persons with overweight and obesity indeed internalize the disadvantaged societal attitudes towards their own ingroup as shown in previous research using explicit selfreport measures (Macho et al, 2021;Pullmer et al, 2021). Interestingly, there was an inverse correlation between BMI and implicit weight bias score, which means that persons with higher BMI showed this preference to a lesser extent.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, for those with low WBI, the positive thinking exercise promoted the greatest self-compassion and lowest negative affect. Given the negative relationship between WBI and self-compassion [ 34 ], the self-compassion exercise may not have provided a new outlook on body image for these participants. It may be that thinking about the positive aspects of one’s life and body acted as a specific type of self-kindness, working to increase an already self-compassionate mindset.…”
Section: Discussionmentioning
confidence: 99%
“…Higher WBI is associated with many negative outcomes, including negative body image [ 30 , 31 ], poor self-esteem (e.g., [ 30 , 31 ]), anxiety [ 32 ], depression (e.g., [ 30 , 33 ]), stress [ 30 ], and negative affect [ 31 ]. In addition, WBI is negatively correlated with self-compassion (e.g., [ 34 ]). One study conducted by Hilbert and colleagues examined the role of self-compassion in the relationship between WBI and outcomes such as health-related quality of life, depression, and somatic symptoms in individuals with higher BMIs [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, whereas internalizing weight stigma may also increase intensely negative emotions toward core aspects of the self (Hilbert et al, 2014;Webb & Hardin, 2016), self-compassion encourages mindfulness, or observing, accepting, and letting go of such emotions (Neff, 2003a(Neff, , 2003b. Supporting this contention, several cross-sectional studies have revealed a negative relationship between trait-level self-compassion and weight bias internalization in weight-diverse populations (Huellemann & Calogero, 2020;Pullmer et al, 2021;Webb & Hardin, 2016). Moreover, selfcompassion interventions have been shown to reduce weight bias internalization in both lower (Forbes et al, 2020) and higher weight (Davies et al, 2022) populations.…”
mentioning
confidence: 97%